THE EFFECT OF TRICHOGASTER PECTORALIS SEPAT FISH ON SWIMMING RESISTANCE IN VARIOUS FLOW SPEEDS - Denita Rahman; Nofrizal Nofrizal; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT This research was conducted in December 2018. The purpose of this study was to determine the characteristics of conjoined sepat fish in each size. The specific purpose of this study is to examine the swimming endurance of conjoined sepat fish, knowing the maximum speed, prolonged speed and brust speed of conjoined sepat fish of various sizes. This research was conducted using an experimental method. The research carried out uses siam size 10 cm with maximum sustained speed <0.51 BL / sec, siam size 15 cm <0.43 BL / sec and for siam size 20 cm <0.24 BL / sec. Siamese sepat fish size 10 cm prolonged speed ranges from 0.51 to 4.73 BL / sec, Siamese sepat fish size 15 cm prolonged speed ranges from 0.43 to 3.84 BL / sec and for Siamese sepat fish size 20 cm speed prolonged ranges between 0.24-3.31 BL / sec. Siamese sepat fish size 10 cm burst speed is 6.73 BL / sec, Siamese sepat fish size 15 cm burst speed is 4.77 BL / sec and for conjoined fish size 20 cm burst speed is 3.84 BL / sec. Swimming speed and endurance of the pool are negatively correlated if the speed is higher then the swimming ability will be reduced and if the swimming speed is high then the endurance of the swimming pool decreases. Keywords: Endurance, swimming speed, flume tank, maximum swimming spe